Constituintes químicos de Maytenus distichophylla Mart. ex Reissek - Duarte, Marcelo Cavalcante (2013)
The family Celastraceae is distributed in tropical and subtropical regions, including North Africa, South America and Asia, particularly in China. It consists of 98 genera and about 1200 species, and in Brazil, this family is represented by four genera: Maytenus Juss., Austroplenckia Lund., Franhofera Mart. and Salacia Mart. The genus Maytenus is one of the largest family Celastraceae, and in Brazil, 76 species are recognized. Maytenus distichophylla Mart. Reissek former is used in folk medicine to treat stomach ulcers and is well adapted to semi-arid Northeast of Brazil. There are no reports of phytochemical and pharmacological study with this species. The aim of this work was to contribute to the phytochemical study of plants of the Brazilian Northeast through the isolation and identification of chemical constituents from leaves and roots of Maytenus distichophylla. Was used for both adsorption and partition chromatography on columns, thin layer chromatography on analytical and preparative. M. distichophylla was collected in the municipality of Maturéia-PB, and identified by Prof.. Dr. Maria de Fátima Agra. The powder obtained from the leaves and roots was subjected to maceration with methanol for 72 hours to yield the methanolic solution which was concentrated on rotaevaporator to give the methanol extract. Leaf extract was partitioned generating phases hexane, chloroform and ethyl acetate. The chloroform phase and ethyl acetate was subjected to chromatographic procedures known pentacyclic triterpenes six isolating the series friedelano, 3β-friedelinol, fridelina 3-oxo-12α-hidroxifriedelano 3-oxo-29α-hidroxifriedelano 3-oxo-30β-hidroxifriedelano and a new natural product the 6β, 12α-dihydroxy-friedelan-1 en-3,16,21-trione called maytensifolona. The chloroform phase roots of M. distichophylla was subjected to Medium Pressure Liquid Chromatography. The group of fractions 115-121 was subjected to High Performance Liquid Chromatography obtaining two sesquiterpene pyridine alkaloids known to wilforina and ebinifolina. Thus, these data corroborate the chemical composition of other species of Maytenus and contribute to the chemical knowledge of M. distichophylla.